Application of Flow Cytometry in Primary Immunodeficiencies: Experience From India - Madkaikar, Manisha Rajan; Shabrish, Snehal; Kulkarni, Manasi; Aluri, Jahnavi; Dalvi, Aparna; Kelkar, Madhura; Gupta, Maya (Frontiers in Immunology, 2019)
Primary immunodeficiency diseases (PID) are clinically and immunologically heterogeneous group of disorders of immune system. Diagnosis of these disorders is often challenging and requires identification of underlying genetic defect complemented by comprehensive evaluation of immune system. Flow cytometry, with its advances in last few decades has emerged as an indispensable tool for enumeration as well as characterization of immune cells. Flowcytometric evaluation of immune system not only provides clues to underlying genetic defect in certain PIDs and helps in functional validation of novel genetic defects, but is also useful in monitoring immune responses following specific therapies. India has witness significant progress in the field of flow cytometry as well as PID over last one decade. Currently, there are seven Federation of Primary Immunodeficiency Diseases (FPID) recognized centers across India, includingtwo Indian Council of Medical research (ICMR) funded centres of excellence for diagnosis and management of PIDs . These centers offer comprehensive care for PIDs including flow cytometry based evaluation. The key question which always remains is how does one select from the wide array of flow cytometry based tests available and whether all these tests should be performed before or after the identification of genetic defects. This becomes crucial especially when resources are limited and patient has to pay for the investigations. In this review, we will share some of our experiences based on evaluation of large cohort of hemophagocytic lymphohistiocytosis, severe combined immunodeficiency and chronic granulomatous disease; and the lessons learnt for optimum use of this powerful technology for diagnosis of these disorders